Bank Trademark Protection in the Digital Era: Comparative Study of Indonesia, United States, Oman - Anak Agung Ayu Ngurah Sri Rahayu Gorda; I Gede Agus Kurniawan; Putu Aras Samsithawrati; Princess Alyssa D. Tee-Anastacio; Musallam Al Awaid (Unnes Law Journal, 2026)
This article examines the protection of bank trademarks in Indonesia, the United States, and Oman, representing Civil Law, Common Law, and a mixed civil–Sharia–GCC legal system respectively. It addresses two main questions: how differences in legal traditions shape the regulation and enforcement of bank trademarks in the digital era, and what model of protection can be formulated to make such protection more adaptive to technology‑based infringements while reinforcing depositor trust. Using a normative legal method with statute and comparative approaches, the study analyzes national trademark and banking regulations, international instruments such as TRIPS and the Madrid Protocol, GCC trademark rules, and relevant case law, interpreted through Lawrence M. Friedman’s legal system theory (structure, substance, and legal culture). The findings show that the United States provides the most advanced protection for bank trademarks through the combination of the Lanham Act, doctrines of likelihood of confusion and dilution, specific tools such as the ACPA and UDRP, and strong coordination with financial regulators. Indonesia and Oman have aligned their substantive rules with international standards, but face structural and cultural constraints, including fragmented inter‑agency coordination, the absence of fast‑track and online dispute resolution mechanisms for digital disputes, and limited institutional capacity. The article proposes a hybrid, trust‑centred model for Indonesia that strengthens substantive norms on bank trademarks, institutional coordination between IP, financial, and digital regulators, and rapid procedures for digital enforcement, while embedding consumer protection, good faith, and amanah as guiding principles.